2019
DOI: 10.1063/1.5095197
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of a simple method prepared polycrystalline SnSe optimized by spark plasma sintering

Abstract: In this study, polycrystalline SnSe was synthesized via a rapid, cost-effective, and large-scale synthesis route. The obtained SnSe powders were pressed into pellets via spark plasma sintering (SPS) at different temperatures. Powder X-ray diffraction (XRD) and field-emission scanning electron microscopy (FESEM) were used to characterize the crystal structures and morphology of the SnSe samples. The XRD results indicate that the orientation factors increase monotonously with the increase of sintering temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…119 The thermoelectric parameters of poly-crystals SnSe are tuned by sintering temperature in the spark plasma sintering (SPS). Zhang et al 120 varied the sintering temperature from 300 to 650 C in SPS and showed that vacancy defects (Se, Sn, and Se-Sn) were responsible for the performance variation. The optimized sintering temperature for the best performance of the material was 550 C. The ZT of 0.47 was observed at 430 C. Ge alloying's effect was studied by varying Ge concentration in the range x ¼ 0.01 to 0.03 (Sn 1Àx Ge x Se).…”
Section: Snse Thermoelectricmentioning
confidence: 99%
See 1 more Smart Citation
“…119 The thermoelectric parameters of poly-crystals SnSe are tuned by sintering temperature in the spark plasma sintering (SPS). Zhang et al 120 varied the sintering temperature from 300 to 650 C in SPS and showed that vacancy defects (Se, Sn, and Se-Sn) were responsible for the performance variation. The optimized sintering temperature for the best performance of the material was 550 C. The ZT of 0.47 was observed at 430 C. Ge alloying's effect was studied by varying Ge concentration in the range x ¼ 0.01 to 0.03 (Sn 1Àx Ge x Se).…”
Section: Snse Thermoelectricmentioning
confidence: 99%
“… 119 The thermoelectric parameters of poly-crystals SnSe are tuned by sintering temperature in the spark plasma sintering (SPS). Zhang et al 120 varied the sintering temperature from 300 to 650 °C in SPS and showed that vacancy defects (Se, Sn, and Se–Sn) were responsible for the performance variation.…”
Section: Various Applicationsmentioning
confidence: 99%
“…(h) Detailed XRD patterns between 28° and 32° in (g). (i) F value of bulk samples in this work and the previous studies. …”
Section: Resultsmentioning
confidence: 67%
“…The variations on the microscopic defects including the defect size and relative concentration in the sample can be detected by positron annihilation spectroscopy. ,, Figure S1 in the Supporting Information shows the peak-normalized positron lifetime spectra of GO-600 and GO-1200. The spectrum of GO-600 shows a longer tail than that of GO-1200, suggesting that there are abundant nanopores in GO-600, which is consistent with nitrogen adsorption/desorption isotherms and SEM results.…”
Section: Resultsmentioning
confidence: 99%